Plasma circulating cell–free DNA integrity and relative telomere length as diagnostic biomarkers for Parkinson’s disease and multiple system atrophy: a cross-sectional study - Chao Ying; Chao Han; Yuan Li; Mingkai Zhang; Shuying Xiao; Lifang Zhao; Hui Zhang; Qian Yu; Jing An; Wei Mao; Yanning Cai (Neural Regeneration Research)
In clinical specialties focusing on neurological disorders, there is a need for comprehensive and integrated non-invasive, sensitive, and specific testing methods. Both Parkinson’s disease and multiple system atrophy are classified as α-synucleinopathies, characterized by abnormal accumulation of α-synuclein protein, which provides a shared pathological background for their comparative study. In addition, both Parkinson’s disease and multiple system atrophy involve neuronal death, a process that may release circulating cell–free DNA (cfDNA) into the bloodstream, leading to specific alterations. This premise formed the basis for investigating cell–free DNA as a potential biomarker. Cell-free DNA has garnered attention for its potential pathological significance, yet its characteristics in the context of Parkinson’s disease and multiple system atrophy are not fully understood. This study investigated the total concentration, nonapoptotic level, integrity, and cell-free DNA relative telomere length of cell-free DNA in the peripheral blood of 171 participants, comprising 76 normal controls, 62 patients with Parkinson’s disease, and 33 patients with multiple system atrophy. In our cohort, 75.8% of patients with Parkinson’s disease (stage 1–2 of Hoehn & Yahr) and 60.6% of patients with multiple system atrophy (disease duration less than 3 years) were in the early stages. The diagnostic potential of the cell-free DNA parameters was evaluated using receiver operating characteristic (ROC) analysis, and their association with disease prevalence was examined through logistic regression models, adjusting for confounders such as age, sex, body mass index, and education level. The results showed that cell-free DNA integrity was significantly elevated in both Parkinson’s disease and multiple system atrophy patients compared with normal controls (P < 0.001 for both groups), whereas cell-free DNA relative telomere length was markedly shorter (P = 0.003 for Parkinson’s disease and P = 0.010 for multiple system atrophy). Receiver operating characteristic analysis indicated that both cell-free DNA integrity and cell-free DNA relative telomere length possessed good diagnostic accuracy for differentiating Parkinson’s disease and multiple system atrophy from normal controls. Specifically, higher cell-free DNA integrity was associated with increased risk of Parkinson’s disease (odds ratio [OR]: 5.72; 95% confidence interval [CI]: 1.54–24.19) and multiple system atrophy (OR: 10.10; 95% CI: 1.55–122.98). Conversely, longer cell-free DNA relative telomere length was linked to reduced risk of Parkinson’s disease (OR: 0.16; 95% CI: 0.04–0.54) and multiple system atrophy (OR: 0.10; 95% CI: 0.01–0.57). These findings suggest that cell-free DNA integrity and cell-free DNA relative telomere length may serve as promising biomarkers for the early diagnosis of Parkinson’s disease and multiple system atrophy, potentially reflecting specific underlying pathophysiological processes of these neurodegenerative disorders.